A giant cavernous hemangioma of the liver extending into the pelvis - Kong, Jiayi (Int J Surg Case Rep, 2015)
INTRODUCTION: Giant cavernous hemangiomas are the most common tumors of the liver, ocurring in up to 20% of the general population. Given their benign course, asymptomatic nature and slow growth rate, treatment is rarely indicated. The case presented herein is unique as it describes an uncommon presentation of this common tumor and the circumstances in which surgical treatment is beneficial. PRESENTATION OF CASE: We present a case of a 66 year-old patient with prostate cancer referred for evaluation of a massive 37 cm giant liver hemangioma, extending into the pelvis and in the planned field of radiation for prostate cancer, exhibiting rapid growth, and associated with significant symptomatology. Given these clinical characteristics, the patient was offered surgery and underwent a left trisectionectomy with an uneventful recovery. The patient's symptoms resolved and he was able to complete radiation to the pelvis. DISCUSSION: In the context of an unusual presentation, this case presentation reviews the typical clinical and imaging characteristics of giant liver hemangiomas and expands on the current indications for treatment, emphasizing the role of enucleation and resection for patients meeting appropriate indications. CONCLUSION: Although liver hemangiomas are extremely common, surgical treatment is rarely required. With appropriate indications, and when enucleation is not feasible or ideal, major liver resection is a safe alternative approach with excellent outcomes when performed in the right setting.